Cyberbullying & Hate Speech An Investigative Field Study of Youth People's Attitudes About The Phenomenon in Libyan Society (Journal of Human Sciences, 2022)
The problem of the study is expressed through a main objective: to identify trends around the phenomenon of Cyber-bullying and Hate Speech, and sub-objectives emerged from it, including an attempt to provide a theoretical analysis of the concept of Cyber-bullying, its forms and the factors causing it. The study also aims to identify the features of Hate Speech deliberated on websites Social media, and suggest some solutions to limit the phenomenon of Cyberbullying and Hate Speech. The study begins from a main question: What are the trends about the phenomenon of Cyberbullying and Hate Speech in Libyan society? The study is considered one of the exploratory studies with the intention of investigating the circumstances of the phenomenon and carrying out following studies on the subject. The study was applied to a survey sample of 38 individuals, and a measure was applied that contains four focuses, consistent with the objectives of the study. It was presented to a number of arbitrators, and was applied electronically on the sample, and several results were reached, including the exposure of many of the sample’s vocabulary to the risk of Cyberbullying, and that there are many effects resulting from the spread of Hate Speech via Facebook  or other communication networks that provoke disorder among the components of society and leads to discord and strife.